Beta oscillations in freely moving Parkinson's subjects are attenuated during deep brain stimulation - Quinn, Emma J.; Blumenfeld, Zack; Velisar, Anca; Koop, Mandy Miller; Shreve, Lauren A.; Trager, Megan H.; Hill, Bruce C.; Kilbane, Camilla; Henderson, Jaimie M.; Brontë-Stewart, Helen (Movement disorders, 2015)
Background Investigations into the effect of deep brain stimulation (DBS) on subthalamic (STN) beta (13‐30 Hz) oscillations have been performed in the perioperative period with the subject tethered to equipment. Using an embedded sensing neurostimulator, this study investigated whether beta power was similar in different resting postures and during forward walking in freely moving subjects with Parkinson's disease (PD) and whether STN DBS attenuated beta power in a voltage‐dependent manner. Methods Subthalamic local field potentials were recorded from the DBS lead, using a sensing neurostimulator (Activa® PC+S, Medtronic, Inc., Food and Drug Administration– Investigational Device Exemption (IDE)‐, institutional review board–approved) from 15 PD subjects (30 STNs) off medication during lying, sitting, and standing, during forward walking, and during randomized periods of 140 Hz DBS at 0 V, 1 V, and 2.5/3 V. Continuous video, limb angular velocity, and forearm electromyography recordings were synchronized with neural recordings. Data were parsed to avoid any movement or electrical artifact during resting states. Results Beta power was similar during lying, sitting, and standing (P = 0.077, n = 28) and during forward walking compared with the averaged resting state (P = 0.466, n = 24), although akinetic rigid PD subjects tended to exhibit decreased beta power when walking. Deep brain stimulation at 3 V and at 1 V attenuated beta power compared with 0 V (P < 0.003, n = 14), and this was voltage dependent (P < 0.001). Conclusions Beta power was conserved during resting and forward walking states and was attenuated in a voltage‐dependent manner during 140‐Hz DBS. Phenotype may be an important consideration if this is used for closed‐loop DBS. © 2015 International Parkinson and Movement Disorder Society